Cracking the Code: Understanding What Influences Online Learning Adoption Among Indonesian Students - Jonathan Gozal (Migration Letters, 2023)
This study examines factors affecting OL adoption among 191 Indonesian students post-COVID-19. It addresses limitations in established models like TRA, TPB, TAM, and UTAUT while introducing new variables. Key findings include: (1) The strong positive effect of FAC and SEF on PEU, suggests that investments in infrastructure and student training could significantly enhance the acceptance and efficacy of OL platforms, (2) The influence of ITR on PUS and, subsequently, INT implies that enhancing ITR capabilities can positively affect both PUS and INT, thereby potentially increasing student engagement and adoption rates, (3) Localized variables like FAC and SEF have a strong positive influence on PEU. These findings contribute to both the theoretical and practical arenas by enhancing existing models and offering context-specific implementation strategies for Indonesia’s emerging edtech sector. This study argues for a more holistic, nuanced approach to understanding OL adoption, providing actionable insights for educators and policymakers.